Green’s function method to the ground state properties of a two-component Bose–Einstein condensate - Liang, C.; Wei, K.; Ye, B.J.; Wen, H.M.; Zhou, X.Y.; Han, R.D. (Физика низких температур, 2011)
The elementary excitation spectrum of a two-component Bose–Einstein condensate is obtained by Green’s function method. It is found to have two branches. In the long-wave limit, the two branches of the excitation spectrum are reduced to one phonon excitation and one single-particle excitation. With the obtained excitation spectrum and the Green’s functions, the depletion of the condensate and the ground state energy have also been calculated in this paper.